Mode-dependent magnonic noise - Ryo Furukawa; Shoki Nezu; Takuro Eguchi; Koji Sekiguchi (NPG Asia Materials)
Abstract The performance of magnonic devices such as converters, switches, and multiplexers greatly depends on magnonic noise. While a peculiar discrete magnonic noise has been previously reported, the sources of underlying magnon dynamics occurring in high-magnon density conditions have not been clarified. Here, zero-span measurements of the spectrum analyzer were recorded to accurately detect magnonic noise as a fluctuation of the spin-wave amplitude. The results of low-frequency magnonic noise demonstrated a spin-wave mode dependency, indicating the existence of a peculiar magnon surface state. Furthermore, the energy thresholds of four-magnon scattering and autooscillation were determined using magnonic white noise. The noise data obtained in this study can help promote theoretical and experimental research on magnons.